2016
DOI: 10.1039/c5nr09093h
|View full text |Cite
|
Sign up to set email alerts
|

Mean-field and linear regime approach to magnetic hyperthermia of core–shell nanoparticles: can tiny nanostructures fight cancer?

Abstract: The phenomenon of heat dissipation by magnetic materials interacting with an alternating magnetic field, known as magnetic hyperthermia, is an emergent and promising therapy for many diseases, mainly cancer. Here, a magnetic hyperthermia model for core-shell nanoparticles is developed. The theoretical calculation, different from previous models, highlights the importance of heterogeneity by identifying the role of surface and core spins on nanoparticle heat generation. We found that the most efficient nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 71 publications
3
40
0
4
Order By: Relevance
“…In the present work, we have demonstrated that surface atoms can respond differently than the core ones, a prominent effect for the smaller fully oxidized derivatives (≤12 nm) of the Fe x O − Fe 3−δ O 4 NCs. Although defect elimination during synthesis can yield nanomagnetic agents (≥20 nm) with enhanced, concurrent diagnostic imaging and thermo-responsive performances [34], structural defects at subcritical particle sizes appear to offer a different exploitable pathway, compatible with the biological limits (e.g., set by toxicity and patient discomfort) [67]. Here, vacancies in self-passivated iron oxides of subcritical size (≤12 nm) act as pinning centers that favor the competition of exchange interactions, thus fostering local anisotropy enhancement.…”
Section: Defect-driven Magnetic Heatingmentioning
confidence: 99%
“…In the present work, we have demonstrated that surface atoms can respond differently than the core ones, a prominent effect for the smaller fully oxidized derivatives (≤12 nm) of the Fe x O − Fe 3−δ O 4 NCs. Although defect elimination during synthesis can yield nanomagnetic agents (≥20 nm) with enhanced, concurrent diagnostic imaging and thermo-responsive performances [34], structural defects at subcritical particle sizes appear to offer a different exploitable pathway, compatible with the biological limits (e.g., set by toxicity and patient discomfort) [67]. Here, vacancies in self-passivated iron oxides of subcritical size (≤12 nm) act as pinning centers that favor the competition of exchange interactions, thus fostering local anisotropy enhancement.…”
Section: Defect-driven Magnetic Heatingmentioning
confidence: 99%
“…In general, it was shown both in simulations and experiment that complex nanoparticles with ferromagnetic core and ferrimagnetic shell morphology can enhance the efficiency of hyperthermia 70 . Another combined theoretical-experimental investigation of the hyperthermia was recently carried out on the level of mean-field for the model core-shell particle 71 . Unfortunately, these approaches cannot be directly applied to predict or analyse the dynamic spectra of magnetic dipolar nanoparticle systems, as they lack an intrinsic feature of the latter, namely, particle polydispersity.…”
Section: Introductionmentioning
confidence: 99%
“…Em geral, esse monitoramento é realizado com a Ressonância Magnética (RM) [3], que é uma técnica cara. Entretanto, tal procedimento não pode ser utilizado no caso da hipertermia magnética com nanopartículas [4][5][6][7][8][9][10], já que esta nanoterapia depende da rotação dos momentos magnéticos das nanopartículas sob ação de campo alternado. Logo, neste caso, não há como ter geração de calor pois o campo magnético de alta intensidade do ímã permanente da RM impossibilita a rotação dos momentos magnéticos das nanopartículas.…”
Section: Introductionunclassified
“…Assim, métodos baseados em sistema de processamento de sinais, simples e de baixo custo, como o sistema de imagens por ultrassom, torna-se uma alternativa interessante. Note, adicionalmente, que o ultrassom pode ser capaz de fornecer uma estimativa de temperatura interna em tempo quase real e ser combinada com várias nanoterapias térmicas, como a hipertermia magnética [4][5][6][7][8][9][10] ou a fototérmica [11].…”
Section: Introductionunclassified